2021
DOI: 10.1111/ctr.14445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk‐stratified mycophenolate dosing in heart transplantation

Abstract: Mycophenolate mofetil (MMF), the prodrug of mycophenolic acid, is a highly effective immunosuppressive agent in heart transplant therapy. While the FDA approved dose is 1500 mg twice daily, dosing is often reduced due to dose-dependent adverse effects.However, empiric MMF dose reductions may lead to sub-therapeutic dosing and impair clinical outcomes. Our single center protocolized a risk-stratified approach based on age and weight to dose 500 mg twice daily or 1000 mg twice daily to patients after heart trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Patients were risk‐stratified based on age and weight; patients ≥60 years old or weighing <60 kg received MMF 0.5 g twice daily, whereas patients <60 years old and weighing >60 kg received MMF 1 g twice daily. Their recently published study of 140 HT recipients found no difference in the 1‐year incidence of high‐grade ACR, graft loss, or mortality, as well as 1‐year incidence of neutropenia, thrombocytopenia, or infection between the two dosing cohorts 27 . These data are intriguing; however, the two MMF doses were prescribed to very different patient populations, and, as such, it is impossible to discern if their equivocal outcomes were derived from the MMF dose or from the inherent differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were risk‐stratified based on age and weight; patients ≥60 years old or weighing <60 kg received MMF 0.5 g twice daily, whereas patients <60 years old and weighing >60 kg received MMF 1 g twice daily. Their recently published study of 140 HT recipients found no difference in the 1‐year incidence of high‐grade ACR, graft loss, or mortality, as well as 1‐year incidence of neutropenia, thrombocytopenia, or infection between the two dosing cohorts 27 . These data are intriguing; however, the two MMF doses were prescribed to very different patient populations, and, as such, it is impossible to discern if their equivocal outcomes were derived from the MMF dose or from the inherent differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the CLEAR study, 26 an initial loading dose of 3 g MMF administered after renal transplant was shown to be correlated with less MPA underexposure and lower rates of early rejection compared to the standard high-grade ACR, graft loss, or mortality, as well as 1-year incidence of neutropenia, thrombocytopenia, or infection between the two dosing cohorts. 27 These data are intriguing; however, the two MMF doses were prescribed to very different patient populations, and, as such, it is impossible to discern if their equivocal outcomes were derived from the MMF dose or from the inherent differences between the groups.…”
Section: F I G U R Ementioning
confidence: 99%